"Aspergilli" on building partitions infested with moulds in residential housing and public utility premises = "Aspergilli" na przegrodach budowlanych zainfekowanych grzybami pleśniowymi pomieszczeń mieszkalnych i użyteczności publicznej - Piontek, Marlena; Łuszczyńska, Katarzyna; Lechów, Hanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Aspergilli constitute a serious risk to the health of the inhabitants of infested rooms. Mycological analysis conducted in buildings infected with moulds in the area of the Lubuskie province (Poland) demonstrated the presence of 9 species of Aspergillus moulds: A. carbonarius A. clavatus, A. flavus, A. fumigatus, A. niger, A. ochraceus, A. terreus, A ustus and A. versicolor.
Keywords: Aspergillus species; mycotoxins; residential housing; mikotoksyny; budownictwo mieszkaniowe; pomieszczenia użyteczności publicznej